PNAEQ - 13 years of post-analytical EQAS in Portugal - Cardoso, Ana (2020)
In the last 13 years, PNAEQ provided a specific program on post-analytical phase. In order to raise the offer of schemes in areas like Thrombosis/ Haemostasis, PNAEQ has established a consortium with ECAT Foundation distributing two more schemes: Post- Analytical Platelet Function and Pre- and Post-Analytical in Haemostasis. Furthermore, five of the analytical schemes organized by PNAEQ include a post-analytical interpretation, such as Blood Morphology, Hemoglobinopathies, Hydatidose, Rubella and Toxoplasmosis. The main objective of implementing specific and integrated programs on post-analytical phase is to evaluate the performance of laboratories on these matters in order to improve their quality service. The specific program on post-analytical phase provided by PNAEQ comprises 6 types of surveys: audits (vertical and presential), case simulation, case-study, document evaluation, quality indicators and questionnaires. Each survey represents a different tool to evaluate several items of the post-analytical process (Table 1), as well as the laboratory collaborators involved in each task (Figure 1). The items in evaluation are annually selected in the PNAEQ Working Group on Pre- and Post-Analytical Phase (created in 2015) and in compliance with the Portuguese Legislation and the ISO 15189:2012(E). Since 2007 PNAEQ has distributed 6 types of tools in the Post-Analytical Phase EQA, stabilizing in 3 of them in the last five years: Audits, Case Simulation and Quality Indicators. The participation rate has been increasing since 2015, which can be due to the multiple actions performed by PNAEQ Working Group on Pre- and Post-Analytical Phase. In addition, the Case Simulation surveys are the most participated (74% average) since the participation depends on PNAEQ. For the future, PNAEQ and the Working Group will work on the continuous update of the tools content distributed in each survey according to international references and the experience of other EQA organizers.